Transport management system (TMS) - Nurkhairunnisa, Zainudin (2012)
Setiausaha Kerajaan Negeri Pahang(SUK)is an organization that is responsible to manage the transportation for other communities such as Institut Kemahiran Ikhtisas Pahang (IKIP),Kolej Islam Pahang Sultan Ahmad Shah (KIPSAS),Kolej Poly-Tech MARA (KPTM) and etc.which are under Setiausaha Kerajaan Negeri Pahang (SUK).It manages the operational of the transportation in matter of booking transport.There are several problems identified when using the manual system. Time to book is limited to working hours when user wants to apply it.Problem occurs when transports have mechanical problems are rented,vehicles that have been double booked and there have been cases when the wrong vehicle has been rented when it has been returned and not serviced.The current system has redundancy,where data cause by the manual system which uses paper to fill the information.Data is also not being kept in the secure location.Information lost is common by using manual system.For the solution of the problems,Transport Management System(TMS)is developed to manage the operational of the transportation in matter of booking process.TMS is a web-based application system. The significant of the system allows the admin, staff, normal user and driver to check the availability of transport directly. Data will be stored in a database.To develop this system, Rapid Application Development (RAD) model had been chosen as a methodology.Hopefully this system can be really helpful and provide services and satisfaction to the user.